Heterotopic Ossification in Vertebral Interlaminar/Interspinous Instrumentation: Report of a Case - Giuseppe Maida; Eleonora Marcati; Silvio Sarubbo (Case Reports in Surgery)
We present here a rare case of heterotopic ossification in interspinous/interlaminar Coflex device. The classical surgical indications for these implants are degenerative canal stenosis, discogenic low back pain, disk herniations, facet syndrome, and instability. However, fractures of spinous processes are a potential risk after interspinous/interlaminar devices’ implantation. Recently, heterotopic ossification, a well-known complication of hip and knee arthroplasty, has been reported after cervical and lumbar prosthesis. We performed undercutting and implantation of the dynamic interspinous/interlaminar device to treat an adult male patient with L4-L5 stenosis. The patient underwent 45-day imaging and clinical followup, and we observed both a neurological and imaging improvement. A CT bone scan, performed 3 years after surgery for recurrence of neurogenic claudication, showed a new stenosis due to an abnormal ossification all over the device. To our knowledge, this is the first reported case of heterotopic ossification in an interspinous/interlaminar dynamic device. Accordingly, we aim to suggest it as a new complication of interspinous/interlaminar devices.